Semantic Functions of Emojis in Computer-Mediated Communication: A Pragmatic and Contextual Analysis - Gabriella Pardede; Damanik , Bernieke Anggita Ristia (Young Journal of Social Sciences and Humanities, 2025)
This study investigates the semantic functions of emojis in computer-mediated communication (CMC) across platforms such as WhatsApp, Twitter, and Instagram. Drawing on a library research method supported by selected conversation samples and relevant scholarly literature, the research explores how emojis contribute to meaning-making in digital interactions. Findings reveal that emojis perform diverse semantic roles, including emotional amplification, lexical substitution, tone modulation, and social signaling. Rather than merely decorative, emojis function as context-sensitive linguistic elements that enhance or replace textual meaning. However, their interpretation is shaped by various factors such as platform norms, interpersonal relationships, and cultural background, often resulting in ambiguity or miscommunication. The study concludes that emojis are dynamic, pragmatic tools in digital discourse that reflect the ongoing evolution of language in online environments. Their strategic use highlights the importance of multimodal literacy in contemporary communication.